1996
DOI: 10.1002/(sici)1098-2795(199608)44:4<499::aid-mrd10>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar and mitochondrial morphology in bovine embryos reconstructed by nuclear transfer

Abstract: The nucleolar and mitochondrial morphology of developing reconstructed bovine nuclear transfer (NT) embryos and stage‐matched in vivo‐produced control embryos were examined under the electron microscope. Each reconstructed embryo at the one‐cell (n = 12), two‐cell (n = 5), three‐cell (n = 3), four‐cell (n = 5), 5–8 cell (n = 5) and blastocyst (n = 3) stages was produced by fusion of a 16–32‐cell‐stage blatomere with an aged enucleated bovine oocyte. The normal and reconstructed embryos showed similar mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…However, mammalian oocytes generally contain spherical immature mitochondria, which are characterised by electron dense matrices with few or no cristae (Hillman and Tasca 1969;Hillman and Hillman 1975;King et al 1996). As development progresses mitochondrial differentiation is observed during progressive cleavages to an elongated shape, with reduced electron density and transverse cristae observed at the blastocyst stage (Van et al 1990;Plante and King 1994;King et al 1996;Crosier et al 2000;Crosier et al 2001;Tao et al 2008). These structural changes are associated with increased metabolic activity, oxygen consumption and CO 2 production observed in the blastocyst Barnett and Bavister 1996).…”
Section: Mixing Of Somatic and Oocyte Mitochondria: Implications For mentioning
confidence: 99%
See 1 more Smart Citation
“…However, mammalian oocytes generally contain spherical immature mitochondria, which are characterised by electron dense matrices with few or no cristae (Hillman and Tasca 1969;Hillman and Hillman 1975;King et al 1996). As development progresses mitochondrial differentiation is observed during progressive cleavages to an elongated shape, with reduced electron density and transverse cristae observed at the blastocyst stage (Van et al 1990;Plante and King 1994;King et al 1996;Crosier et al 2000;Crosier et al 2001;Tao et al 2008). These structural changes are associated with increased metabolic activity, oxygen consumption and CO 2 production observed in the blastocyst Barnett and Bavister 1996).…”
Section: Mixing Of Somatic and Oocyte Mitochondria: Implications For mentioning
confidence: 99%
“…Nuclear transfer embryos display numerous ultrastructural changes compared to in vitro produced (IVP) and in vivo embryos (King et al 1996). Nuclear transfer embryos produced using embryonic (King et al 1996), foetal (Zhong et al 2007;Zhong et al 2008) or adult (Tao et al 2008;Han et al 2008) donor cells demonstrate heterogenous morphologies not seen in IVP or in vivo embryos that persist for several cleavages.…”
Section: Mixing Of Somatic and Oocyte Mitochondria: Implications For mentioning
confidence: 99%
“…King et al (1996) reported that, in bovine cloned embryos, mature mitochondria that were probably carried along with the donor cells were observed at the one-to four-cell stages. That is why it is speculated that mature autoreplicating mitochondria, transferred with nuclear donor embryonic or somatic cells into recipient ooplasts, may be broken down in the blastomere cytoplasm of reconstituted embryos during the above mentioned morphological transformation and genomic maturation of mitochondria during preimplantation embryogenesis (Takeda et al, 1999;Do et al, 2001;Meirelles et al, 2001).…”
Section: Conservation Of Uniparental (Maternal) Inheritance Of the MImentioning
confidence: 99%
“…Bovine cloned embryos display nucleoli with a transcriptionally active morphology, indicating that reprogramming of rRNA genes is slow (King et al, 1996;Lavoir et al, 1997). They also display heterogeneity in mitochondrial morphology, indicating possible alterations in mitochondrial gene expression (King et al, 1996).…”
Section: Consequences Of Aberrant Epigenetic Reprogrammingmentioning
confidence: 99%
“…They also display heterogeneity in mitochondrial morphology, indicating possible alterations in mitochondrial gene expression (King et al, 1996).…”
Section: Consequences Of Aberrant Epigenetic Reprogrammingmentioning
confidence: 99%